(3OjhGf HhQj Hf CjhHs - (3eLO GdOjf CHhSYjO HhQj Hf GjhH Hf TGPj Hf eQhGf,J (B579 (3g` s ((3YHOGddg Hf gGOj s)
(3ChdgG (B:s
(3Ndb Gdghi OGA HZjQ OhGA aYdjdg CHOkG HZjQ TaGA s
(3BNQgG (B:s
(3hEfj dCTJTaj ef GdHjf HGdQOi hMSHc OGA Cf JQi GdehJ TGajkG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B207 - (3U(B296s
(3oeQJH Ydi GdbhGajs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B56s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B51 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B780s
Keywords: (3GdCOHs